Peran apoteker dalam menangani swamedikasi kasus minor illnes di apotek - Burhanudin, Yasmin Ramadania; Gozali , Dolih (Journal of Pharmaceutical and Sciences, 2024)
Health is a crucial part of life. An individual's level of living is reflected in their state of health. The most important thing to do if the person has health issues at any point is to make every effort to heal through self-medication. Preparing this article is to evaluate how healthy pharmacists perform self-medication and make drug selections to enhance public health. Self-medication is typically used to cure common minor health issues, such as skin infections, worm infections, coughs, influenza, stomach ulcers, dizziness, coughing, diarrhea, and coughing up blood. The research in question was derived from search engine results and examined pharmacists' capacity to prescribe medications for mild ailments. According to the search results in several journals, the overall accuracy rate of recommendations for children experiencing acute diarrhea is 13.09%; for diarrhea, including blood, it is 34.52%; for dyspepsia due to side effects of Diclofenac Sodium, it is 21%; and for dyspepsia without alarm, symptoms is 83%. According to research findings, enhancing pharmacists' capacity to offer drug guidance while facilitating self-medication is crucial.